Modelling and numerical simulation of hygrothermal transfer through a building wall for locations subjected to outdoor conditions in Sub-Saharan Africa - (:unkn) unknown (My University, 2019)
In the building sector, the improvement of the heat and mass insulation of the walls can reduce the values of the global energy demand and the CO2 emission. A coupled one-dimensional heat and mass transfer model through a building wall was proposed in this study. The governing equations integrate the influences of Dufour and Soret effects and are numerically resolved using FORTRAN 90 and finite difference method in Crank-Nicolson scheme. Gauss-Seidel relaxation iteration method is used in order to generate the numerical solutions. The accuracy of the model was evaluated with experimental data on wooden wall and concrete wall from literature. A very satisfactory agreement is noted between the numerical predictions, experimental observations and physical phenomenon obtained. The model was further used to simulate the hygrothermal transfer through five tropical woods used as building walls in sub-Saharan African region after integration of outdoor conditions. These five woods have densities ranging from 430 to 800 kg/m3 and the conditions of the interior air were fixed to maintain a comfortable state for the occupants. Twelve towns located within latitudes 4.33°S to 12.37°N in Sub – Saharan Africa were used to discuss the results given by the model. At the end, influences of anatomical direction, tropical wood types, wall thickness, latitudes of the locations and solar radiation on evolutions of temperature and moisture content in the wall are studied. Our results showed that these parameters have significant effects on temperature and moisture content propagation within the wall. Using a wooden wall of 5 cm thickness, it is possible to reduce significantly the effect of the exterior heat.
Keywords: African Research